Analysis of Metallic Nanoparticles (Cu, Al2O3, and SWCNTs) on Magnetohydrodynamics Water-Based Nanofluid through a Porous Medium. (14th February 2022) - Pattnaik, P. K.; Parida, S. K.; Mishra, S. R.; Abbas, M. Ali; Bhatti, M. M.
Abstract : In this communication, the effect of the addition of the copper (Cu), aluminum oxide (Al2 O3 ), and single-wall carbon nanotubes (SWCNTs) metallic nanoparticles on the magnetohydrodynamics (MHD) water-based flow over a porous elastic surface is explored. The objective of the work is to include the radiative effect that interacts with the metallic nanoparticles due to permeability of the surface. The significance of this study stems from the fact that the design of various equipment, such as nuclear power plants, gas turbines, propulsion devices for aircraft, and missiles, is dependent on radiative heat transfer. To formulate the mathematical modelling, similarity transformations were used, and nonlinear differential equations were obtained. To solve the formulated nonlinear differential equations, the Runge–Kutta fourth-order numerical scheme is used in conjunction with the shooting technique. The behavior of velocity profile and temperature profile has been discussed in detail and also engineering quantities such as Nusselt and Sherwood number which are calculated. Furthermore, the addition of metallic nanoparticles enhanced the nanofluid properties for energy transfer enrichment and found many applications in various fields of science and technology.